Combining impact monitoring mouthguards and blood biomarkers to monitor head impacts among Muay Thai athletes – A case study - Mikael Swarén; Joel Simrén; Hanna Huber; Henrik Zetterberg (JSAMS Plus, 2023)
Objective: To investigate the relationship between head impact characteristics and the levels of blood biomarkers associated with brain injury, neurofilament light (NfL) and glial fibrillary acidic protein (GFAP). Methods: Four elite amateur Muay Thai athletes were equipped with impact monitoring mouthguards, collecting linear and rotational acceleration data during a period of eight weeks. Capillary blood samples were collected after each period of sparring sessions to analyse the levels of NfL and GFAP. Results: On a group level, mean GFAP levels were negatively correlated to mean impacts per session (p ​< ​0.05). Two athletes had significant correlations between head impact characteristics and the levels of NfL and/or GFAP. Conclusions: The results indicate that NfL and GFAP might responded differently to linear and rotational accelerations and/or that the effect of different types of accelerations on brain tissue integrity is individual. The methods used could be useful to monitor brain health in different impacts sports.